Intermidialidade, cinema e pintura na trilogia o Poderoso Chefão, de Francis Ford Coppola - Sirino, Taylla Maria Machado (2023)
Under the perspective of intermediality studies, this research aims to analyze the influence of Baroque painters who were precursors of Tenebrism on the composition of the film photography in "The Godfather," directed by filmmaker Francis Ford Coppola, parts I, II, and III, filmed in 1972, 1974, and 1990, respectively. The emphasis of this analysis is based on the work of the cinematographer for these films, Gordon Willis, renowned as the "prince of darkness" for his aesthetic choice of dark and tonally contrasting lighting reminiscent of the Renaissance painting technique known as chiaroscuro. This technique was transposed into cinematography and had previously influenced film noir and German expressionism, proving essential in constructing pictorial visuality in the film photography of "The Godfather" trilogy by Francis Ford Coppola. Subsequently, we will analyze frames as examples of intermedial transposition from painting to cinema, following the principles of intermediality postulated by Rajewski (2015). In the context of film photography composition, relevant theoretical anchors for this study include "A Estética do Filme" (1994) by Jacques Aumont et al., "O Cinema" (1991) by André Bazin, and "O Olho Interminável: Cinema e Pintura" (2004) by Jacques Aumont. Additionally, we draw on Walter Moser's theoretical assumptions (2006), who considers painting as an ancestral art of cinema, and interviews with the cinematographer Gordon Willis. Film frames from "The Godfather," parts I, II, and III, as well as paintings by Michelangelo Merisi da Caravaggio, Jacobo Tintoretto, Rembrandt Harmenszoon van Rijn, Jacques-Louis David, and Gerard van Honthorst, serve as foundational elements for the proposed comparative analysi